(untitled) (Progress Annals: Journal of Progressive Research, 2024)
Developing critical thinking of children while using digital technologies is shown in this paper as digital learning platforms provide opportunities for children to engage with diverse cultures and perspectives, fostering empathy and understanding. Integrating critical thinking exercises into digital language learning prepares children for the demands of future careers, where cross-cultural communication and problem-solving skills are paramount.